ABOUT STANDARD JURISPRUDENCE OF THE SUPREME COURT OF THE REPUBLIC OF KAZAKHSTAN - Yusupova, Гульмира Хасимовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In this paper, the author defines the normative jurisprudence of the Supreme Court of the Republic of Kazakhstan as a special kind of activity of the highest judicial body for the formation of the rules of interpretation.